The Role of Classroom Teachers in Integrating Deep Learning into the Merdeka Curriculum Based on Islamic Values in Elementary Schools - Meliyawati Meliyawati; Feri Riski Dinata (Bulletin of Indonesian Islamic Studies, 2025)
Basic education plays a strategic role in character formation and competency development in the 21st century, so pedagogical innovation is needed that is in line with the implementation of the merdeka Curriculum. The purpose of this study is to examine the role of classroom teachers in the implementation of deep learning in a pedagogical context based on Islamic values in elementary schools. This study uses a qualitative approach with a case study design, the data in this study was obtained through observation, interviews and documentation of teachers at Sekolah Dasar Negeri 01 Pisang Baru (Pisang Baru Public Elementary School 01). The results of the study revealed that teachers have a crucial role as designers, facilitators, and role models in associating the principles of deep learning with the values of honesty, responsibility, and empathy. This integration creates a learning process that is reflective, in-depth and oriented towards strengthening the character of students. This study provides a conceptual and practical contribution to an integrative model that combines pedagogical deep learning methods with Islamic values in the context of an merdeka curriculum.